2012
DOI: 10.4028/www.scientific.net/amr.545.312
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Conductivity of PVC-NH<sub>4</sub>I-EC Proton Conducting Polymer Electrolytes

Abstract: Poly(vinyl) chloride (PVC)-NH4I-EC films have been prepared by solution cast technique. The sample containing 30 wt. % NH4I exhibited highest room temperature conductivity of 4.60 × 10-7S cm-1. The conductivity increased to 1.08 × 10-6Scm-1when 15 wt. % of ethylene carbonate (EC) was added to 70 wt. % PVC - 30 wt. % NH4I. Fourier Transform Infrared (FTIR) showed evidence of polymer–salt complexation while DSC showed increase in glass transition temperature (Tg) of PVC -NH4I - EC polymer electrolytes. The condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…Nevertheless, it is remarkable to note that at nearly 60 o C, the conductivity was significantly increased for both polymer electrolytes. This remarkable change in conductivity is correlated with the glass temperature T of PVC, which is measured to be about 60 o C as discussed in previous studies [6,7]. Previous studies have shown that ionic conductivity is closely related to T g [1,6].…”
Section: Temperature Dependent Conductivitysupporting
confidence: 69%
See 1 more Smart Citation
“…Nevertheless, it is remarkable to note that at nearly 60 o C, the conductivity was significantly increased for both polymer electrolytes. This remarkable change in conductivity is correlated with the glass temperature T of PVC, which is measured to be about 60 o C as discussed in previous studies [6,7]. Previous studies have shown that ionic conductivity is closely related to T g [1,6].…”
Section: Temperature Dependent Conductivitysupporting
confidence: 69%
“…This remarkable change in conductivity is correlated with the glass temperature T of PVC, which is measured to be about 60 o C as discussed in previous studies [6,7]. Previous studies have shown that ionic conductivity is closely related to T g [1,6]. Preceding to this change, polymer electrolytes are in a glassy state, where the polymer segments have limited movement and ions are stimulated using hopping mechanism [1].…”
Section: Temperature Dependent Conductivitysupporting
confidence: 58%
“…In such systems, the charge carriers are H + ions that come from ammonium ions of the salts. The conduction of the H + ions occurs through exchange of H + ions between complexed sites [3,4]. In the present study, proton conducting polymer electrolytes were prepared using PEMA as the host.…”
Section: Introductionmentioning
confidence: 99%
“…Four well-known theoretical hopping/tunneling models typically used to determine the conduction mechanism in polymer electrolyte systems are correlated barrier hopping (CBH) [11,12], small polaron hopping (SPH) [13], quantum mechanical tunneling (QMT) [14,15], and overlapping large polaron tunneling (OLPT) [16][17][18] models. These theories were based on the Universal Power Law or also known as Universal Dielectric Response as originally proposed by Jonscher in 1977 to understand ion dynamics.…”
Section: Frequency Dependence Studiesmentioning
confidence: 99%